Performance Disparity in Mathematics between male and female Students in Selected Secondary Schools in Kamuganguzi Subcounty, Kabale District. - Amos, Musimenta (Kabale University, 2020)
Gender has long been considered as a factor contributing to differences in performances of male and female students in all cycles of learning. Although male and female students are taught together in the same classes countrywide, there have been differences in academic performance in Mathematics. Thus, the aim of this study was to compare males and females’ performance in Mathematics in selected secondary schools in Kabale district. The study was guided by objectives which were to compare the difference in performance in Mathematics among boys and girls, examine the factors accounting for the differences in performance between boys and girls and, to establish the effect of gender on academic performance. Cross sectional research design was used and a sample size of two hundred thirty respondents was used. Purposive and simple random sampling techniques were used to select respondents. Data collection was done by using questionnaires, interviews and documentary review. The analysis was done using Statistical Package for Social Scientists (SPSS). Analysis of variance was done for teaching methods and academic performance and correlation analysis were done for the effect of gender on academic performance in Mathematics. The study result showed that male students had a mean of 6.94 with a standard deviation of 4.67 while female students had a mean of 6.81 with a standard deviation of 4.33. This indicated that male students outperformed female students in Mathematics in the selected secondary schools in Kamuganguzi Sub County. Findings on the teaching methods indicated that the mean score was highest (10.14) for the classes where question/answer method was used with a standard deviation of 1.96 followed by discussion method (6.48) and a standard deviation of 0.82. The mean score obtained in the classes where demonstration method was used was 5.80 with a standard deviation of 2.76 and the lowest mean (4.12) was scored by the students who were taught using lecture method was used. In addition, there was a very strong positive correlation coefficient (0.928) between gender (male and female students) and academic performance in Mathematics.